1990
DOI: 10.1111/j.1469-8137.1990.tb00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Mcchanism of flood tolerance in reed, Phragmites australis (Cav.) Trin. ex Steudel

Abstract: SUMMARYImportant factors, such as porosity, respirational O^ consumption, O^ release of the roots and iron oxidation on the root surface, which are involved in the flood tolerance of Phragmites australis were investigated in northern Germany, The porosity of the different organs was determined as 58 % for rhizomes, 42 % for culms and 23-38 % for adventitious roots. Mean respirational O^ consumption of below ground organs was measured at 5, 10, 15 and 20 °C as respectively 0-25, 0-5, 0-8 and 1-75 nmol O.^ g"' d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 21 publications
1
35
3
Order By: Relevance
“…Hefting et al (2003) measured values up to 183 kg N ha −1 year −1 in a grassland riparian buffer zone with a water table just below sediment surface. The results of the denitrification measurements do not support the assumption that vegetation stimulates denitrification by aerating the soil via root gas exchange (Matsui and Tsuchiya 2006;Gries et al 1990). In our experiments vegetation presence had a negative influence on the denitrification rate.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Hefting et al (2003) measured values up to 183 kg N ha −1 year −1 in a grassland riparian buffer zone with a water table just below sediment surface. The results of the denitrification measurements do not support the assumption that vegetation stimulates denitrification by aerating the soil via root gas exchange (Matsui and Tsuchiya 2006;Gries et al 1990). In our experiments vegetation presence had a negative influence on the denitrification rate.…”
Section: Discussioncontrasting
confidence: 44%
“…Nutrient concentrations may have been reduced by direct uptake by helophytes (Huet et al 2005). Another possibility is the oxidation of the sediment by root gas exchange (Matsui and Tsuchiya 2006;Gries et al 1990). A higher frequency of oxic microsites would increase nitrification rates (Tanner et al 1999;Patrick and Reddy 1976) and result in adsorption of phosphate to oxidized iron.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that increased oxygen availability stimulates microbial processes that would otherwise be retarded by cold. It is well documented that many wetland plant species release oxygen from their roots in varying amounts (Armstrong, 1971;Gries et al, 1990;Sorrell, 1999), and our results confirm this for many of the species studied. Because domestic wastewater has abundant organic carbon, treatment is often limited by oxygen, the most energetically favorable electron acceptor.…”
Section: Discussionsupporting
confidence: 79%
“…Armstrong (1971) and Howes and Teal (1994) found greater ROL at lower temperatures. Gries et al (1990) and Moog and Bruggemann (1998) found that enhanced ROL was associated with reduced root respiration at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out on morphology and physiology of Spartina and Phragmites individually (Gries et al 1990;Hellings and Gallagher 1992;Naidoo et al 1992;Hwang and Morris 1994;Armstrong et al 1996;Colmer et al 1996;Wijte and Gallagher 1996;Lissner and Schierup 1997;Chambers et al 1998). Few studies, however, have been carried out to examine whether and how the competitive outcome between Phragmites and Spartina is affected by the growing conditions.…”
Section: Introductionmentioning
confidence: 99%